Intermittent high dose proton pump inhibitor enhances the antitumor effects of chemotherapy in metastatic breast cancer. Issue 1 (December 2015) - Wang, Bi-Yun; Zhang, Jian; Wang, Jia-Lei; Sun, Si; Wang, Zhong-Hua; Wang, Lei-Ping; Zhang, Qun-Ling; Lv, Fang-Fang; Cao, En-Ying; Shao, Zhi-Min; Fais, Stefano; Hu, Xi-Chun
Abstract Background Acidity is a hallmark of malignant tumor, representing a very efficient mechanism of chemoresistance. Proton pump inhibitors (PPI) at high dosage have been shown to sensitize chemoresistant human tumor cells and tumors to cytotoxic molecules. The aim of this pilot study was to investigate the efficacy of PPI in improving the clinical outcome of docetaxel + cisplatin regimen in patients with metastatic breast cancer (MBC). Methods Patients enrolled were randomly assigned to three arms: Arm A, docetaxel 75 mg/m2 followed by cisplatin 75 mg/m2 on d4, repeated every 21 days with a maximum of 6 cycles; Arm B, the same chemotherapy preceded by three days esomeprazole (ESOM) 80 mg p.o. bid, beginning on d1 repeated weekly. Weekly intermittent administration of ESOM (3 days on 4 days off) was maintained up to maximum 66 weeks; Arm C, the same as Arm B with the only difference being dose of ESOM at 100 mg p.o. bid. The primary endpoint was response rate. Results Ninety-four patients were randomly assigned and underwent at least one injection of chemotherapy. Response rates for arm A, B and C were 46.9, 71.0, and 64.5 %, respectively. Median TTP for arm A (n = 32), B (n = 31), C (n = 31) were 8.7, 9.4, and 9.7 months, respectively. A significant difference was observed between patients who had taken PPI and who not with ORR (67.7 % vs. 46.9 %, p = 0.049) and median TTP (9.7 months vs. 8.7 months, p = 0.045). Exploratory analysis showed that among 15 patients with triple negative breast cancer (TNBC), this difference was bigger with median TTP of 10.7 and 5.8 months, respectively (p = 0.011). PPI combination showed a marked effect on OS as well, while with a borderline significance (29.9 vs. 19.2 months, p = 0.090). No additional toxicity was observed with PPI. Conclusions The results of this pilot clinical trial showed that intermittent high dose PPI enhance the antitumor effects of chemotherapy in MBC patients without evidence of additional toxicity, which requires urgent validation in a multicenter, randomized, phase III trial. Trial registration Clinicaltrials.gov identifier:NCT01069081 .